Tinjauan Hukum Pidana Islam terhadap Kejahatan Korporasi dalam Lingkungan Hidup - Imaduddin, Ahmad (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2019)
Corporate crime is indeed significant to discuss, because it cannot be denied that the role of the corporation is now very important. In this case there needs to be strict criminal liability, so that corporations do not pollute rivers, beaches or endanger the lives of workers or the public or others. Also so that the corporation does not become a fertile ground for corruption. This paper comes with the aim of wanting to know the review of Islamic criminal law against corporate crime. At the end of the paper, it is concluded that: (1) corporate crime in Law No. 23/1997 concerning Environmental Management is an action taken by a company, union, foundation or other organization that results in environmental pollution and / or damage, while sanctions for perpetrators of pollution and/or environmental damage are in the form of fines (ranging from Rp. 100,000. 000.00 to IDR 750,000,000.00) and / or imprisonment (ranging from 3 years to 15 years). And (2) that corporate crime and sanctions are in line and not in conflict with Islamic criminal law, which is included in the category jarimah ta'zir. Abstrak: Kejahatan korporasi memang signifikan untuk dibahas, karena tidak bisa dipungkiri bahwa peran korporasi saat ini menjadi sangat penting. Dalam hal ini perlu ada pertanggungjawaban pidana secara tegas, agar korporasi tidak mencemari sungai, pantai atau membahayakan jiwa pekerja atau publik atau lainnya. Juga agar korporasi tidak menjadi tempat tumbuh suburnya tempat korupsi. Tulisan ini hadir dengan tujuan ingin mengetahui tinjauan hukum pidana Islam terhadap kejahatan korporasi. Di akhir tulisan disimpulkan, bahwa: (1) kejahatan korporasi dalam UU No. 23/1997 tentang Pengelolaan Lingkungan Hidup merupakan tindakan yang dilakukan oleh perseroan, perserikatan, yayasan atau organisasi lain yang mengakibatkan pencemaran dan/atau perusakan lingkungan hidup, sedangkan sanksi bagi pelaku pencemaran dan/atau perusakan lingkungan adalah berupa denda (berkisar antara Rp. 100.000.000,00 sampai dengan Rp. 750.000.000,00) dan/atau pidana penjara (berkisar antara 3 tahunsampai dengan 15 tahun). Dan (2) bahwa kejahatan korporasi dan sanksinya tersebut sejalan dan tidak bertentangan dengan hukum pidana Islam, di mana termasuk dalam kategori jarimah ta'zir.